Ramla : city of Muslim Palestine, 715-1917 : studies in history, archaeology and architecture - Petersen, Andrew; Pringle, Denys; Abu-Munshar, Maher Y. (Archaeopress archaeology., 2021)
Ramlapresents a comprehensive overview of the history, archaeology and architecture of the city of Ramla from the time of its foundation as the capital of Umayyad Palestine around 715 until the end of Ottoman rule in 1917. It begins with a historical outline covering in turn the early Islamic (Robert Hoyland), Crusader (Peter Edbury), Ayyubid-Mamluk (Donald S. Richards) and Ottoman periods (Matthew Elliot). In the archaeological section, Gideon Avni's synthesis of the results of excavations on the early Islamic city is followed by discussions of the Umayyad-period aqueduct (Amir Gorzalczany) and the historical interpretation of First World War aerial photographs (Benjamin Z. Kedar). Architectural studies include a complete corpus of the surviving Muslim buildings (Andrew Petersen), a reassessment of the remains of the White Mosque (Michael H. Burgoyne), an account of the Christian buildings (Denys Pringle), and an analysis of late Ottoman alterations to the Great Mosque (Katia Cytryn-Silverman). The final section on numismatics and epigraphy includes chapters on the coinage of Umayyad Ramla (Nikolaus Schindel), the Arabic inscriptions (Mehmet Tütüncü) and late medieval Christian pilgrims' graffiti (Denys Pringle). The volume concludes with three appendices, including a hitherto unpublished report on the White Mosque (1919-20) by K.A.C. Creswell, a gazetteer of settlements in the Crusader lordships of Ramla, Lydda and Mirabel, and the endowment deed for a house dated 1713 (Maher Abu-Munshar).--